Existence of Islamic Boarding School Sufism in the Digital Age: Buya Syakur Yasin's Sufism Moderation Thoughts - Nikmah, Shofiatun; Muluk, Muchamad Saiful (Universitas Islam Negeri Raden Intan Lampung, 2022)
The existence of Sufism took part in filling the empty space in the midst of Indonesian people's lives from the colonial era to the current digital era, one of the thoughts of Sufism in Indonesia is Buya Syakur Yasin with his Sufism moderation thoughts. This research looks at the dynamics of Islamic boarding school Sufism from time to time, as well as the role of Buya Syakur Yasin in spreading religious moderation with a Sufistic perspective in the digital era. This study uses a qualitative method with a socio-historical approach to understand holistically from time to time the dynamics of Islamic boarding school tasawuf and content-analysis as an analytical tool in capturing the meaning of Buya Syakur Yasin's thoughts through his Youtube Channel. Research shows that the dynamics of Sufism in Islamic boarding schools is divided into four typologies: the early Islamic era, the colonial era, the modern era and the digital era. Meanwhile, Buya Syakur Yasin, through a digital platform, develops an understanding of moderate Sufism which is closely related to humanistic Sufism, where human values become common consciousness to foster religious moderation in perspective and behavior in everyday life.